Socioeconomic status on pregnancy outcomes in Indian scenario - Patel, Santosh; Jain, Swati; Babu, G. Chitti; Kumar, Masuram Bharath (International Journal Of Community Medicine And Public Health, 2020)
Background: Socioeconomic status (SES) is one of the main components related with clinical outcomes. At the point when SES is low, clinical consideration is lacking and this has been credited to unfriendly results include anemia and pregnancy-induced hypertension. Methods: The study was conducted in the Department of obstetrics and gynecology and the Department of Community Medicine of a private Hospital, for one year. Data was collected using a questionnaire by interview. Study variables included monthly income (i.e. <Rs. 6000, 6000-12000 and >Rs. 12000) lifestyle, eating habits and type and amount of food consumed, a pattern of health care utilization, chronic illness, history of illicit and employment status of husband and women. Results: In the current study, the majority of 83 (67.4%) participants were between 18 and 19 years of age, with their mean age being 18.1±2.3 years, and 108 (87.8%) were Hindus by religion. As many as 113 (91.8%) teens were housewives and 42 (34.1%) of their husbands were factory workers. Most 59 (47.9%) of the teens belonged to class IV socioeconomic status as per modified BG Prasad classification and 93 (75.6%) were living in a joint family. Conclusions: The mean age of participants was 18.1 years, and that of marriage was 17 years and this occurrence of pregnancy in teenagers leads to adverse outcomes. Thus, periodic information, education and communication activities have to be held, and the child marriage act has to be strictly enforced to improve their health.